The Practice of Buying and Selling Used Clothes According to the Perspective of Islamic Law - Suryo Noto Pratama; Haeran; Reza Okva Marwendi; Daud; Siti Fatimah (Zabags Qu Publish, 2025)
This article examines the dynamics of the second-hand clothing trade in Indonesia, which has grown significantly in response to rising demand for affordable apparel while simultaneously raising concerns related to hygiene, consumer protection, and compliance with Islamic principles. The main objective of this study is to analyze the legal, economic, and religious dimensions of this practice, particularly its implications for consumer rights and alignment with maqasid shariah. Employing a systematic literature review, the research systematically maps recent studies from reputable journals over the past five years, classifies their findings into key themes, and synthesizes insights to highlight research gaps. The results reveal that while the trade in second-hand clothing provides economic opportunities and fulfills social needs, it also carries substantial risks in terms of health, safety, and halal assurance. These findings underscore the need for more comprehensive regulation and awareness to ensure that this practice remains both safe and compliant with Islamic values. The study’s contribution lies in its integrative approach, which connects economic accessibility with ethical and legal accountability, offering a valuable reference for policymakers, academics, and practitioners concerned with sustainable consumption and Islamic economic law.